2011
DOI: 10.1210/jc.2010-1193
|View full text |Cite
|
Sign up to set email alerts
|

Modified-Release Recombinant Human TSH (MRrhTSH) Augments the Effect of131I Therapy in Benign Multinodular Goiter: Results from a Multicenter International, Randomized, Placebo-Controlled Study

Abstract: In this dose-selection study, 0.03 mg MRrhTSH was the most efficacious dose as an adjuvant to (131)I therapy of MG. It was well tolerated and significantly augmented the effect of (131)I therapy in the short term. Larger studies with long-term follow-up are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 36 publications
2
54
0
1
Order By: Relevance
“…As such areas concentrate 131 I very weakly, the efficacy of this treatment is compromised. The use of low doses of recombinant TSH significantly increases 131 I uptake in such patients and allows even low activities to efficiently reduce the goiter size by 30 to 50% in one year (60)(61)(62).…”
Section: Recommendation 20mentioning
confidence: 99%
“…As such areas concentrate 131 I very weakly, the efficacy of this treatment is compromised. The use of low doses of recombinant TSH significantly increases 131 I uptake in such patients and allows even low activities to efficiently reduce the goiter size by 30 to 50% in one year (60)(61)(62).…”
Section: Recommendation 20mentioning
confidence: 99%
“…rhTSH in a low single dose increases 131 I uptake by two-to fourfold, and similar therapeutic effects (in comparison with higher 131 I activities without rhTSH prestimulation), and with lower exposure of extrathyroidal tissues to radiation (23 given (11,14,16,19,24,25). Overall, it has been shown that rhTSH doses lower than 0.1 mg do not cause acute increases in TV or thyroid hormone levels (26).…”
Section: Introductionmentioning
confidence: 84%
“…MRrhTSH has an altered PK with a later T max than aqueous rhTSH. Potentially, MRrhTSH could reduce the side effects due to altered pharmacokinetics, with a delayed time to reach the maximum TSH concentration when compared with aqueous rhTSH (19). Our third study compared two different rhTSH doses .…”
Section: Rhtsh and 131 I For Mngmentioning
confidence: 96%
See 2 more Smart Citations